Effectiveness of influenza vaccination in elderly outpatients in São Paulo city, Brazil - GUTIERREZ, Eliana Battaggia; LI, Ho Yeh; SANTOS, Ana Catarina De Seixas; LOPES, Marta Heloísa (Revista do Instituto de Medicina Tropical de São Paulo, 2001)
To investigate the effectiveness of the influenza vaccine in a population of elderly outpatients, we compared the occurrence and frequency of influenza like illness (ILI), respiratory illness and hospitalization in vaccinated and non-vaccinated subjects. All the outcomes were clinically defined. The two groups were similar with respect to demographics, health situation and habits. The influenza vaccine contributed to the protection of the elderly investigated, since the vaccinated subjects referred a significantly lower number of ILI than the non-vaccinated. There is a need for more studies about the effectiveness of the influenza vaccine in our country in elderly and other groups of our population.